An empirical study on the influencing factors of mobile health apps acceptance among silver generation in China: an extended STAM - Xie, Qing; Mahomed, Anuar Shah Bali; Mohamed, Rosmah; Subramaniam, Anusuiya (Human Resources Management Academic Research Society (HRMARS), 2024)
Mobile health apps acceptance is the necessary element for healthcare business success and market expanded. Hence, the current study examines features that impact the acceptance of mHealth apps among silver generation mobile users in China. Companion presence, initial trust and the Senior Technology Acceptance Model (STAM) was employed as influencing factors. Questionnaires for data collection was extracted and data was collected from 641 responses using the purposive sampling approach. Smart-PLS was applied to examine the relationships among variables. The results indicated that companion presence and initial trust have positive nexuses with mHealth apps acceptance intention. This study contributes new insights to evaluating mHealth apps acceptance by considering the effects of companion roles of apps and also offers substantial contributions for practitioners to improving the app features